Young athletes` time perspective as a factor in the development of sports motivation - Popovych, I.; Chervinska, I.; Kazibekova, V.; Vasylyk, M.; Verbeschuk, S.; Gniezdilova, V. (Journal of Physical Education and Sport, 2022)
The purpose of the empirical study was to establish and substantiate the correlations between the dominant types of young athletes` time perspectives and their motivations for participating in sports; to compare motivations for sports among respondents with optimal (Group 2) and general time perspective profiles (Group 1). Research Methods: "Zimbardo Time Perspective Inventory" ("ZTPI") (Zimbardo & Gonzalez, 1984) and "Motives for Playing Sports" ("MPS") (Shaboltas, 2004) were used as valid test methods that were relevant to the subject of the study; targeted observation using standard protocols; methods of mathematical processing of empirical data were used. Results. The feasibility of conducting a time perspective study on the continuum of motivation of young athletes: "Need (past) - Sports Activity Plan (present) - Goal (future)" was substantiated. The time perspective Future (F) was discovered to have the most statistical relationships - eight (p<=.05; p<=.01). The strongest positive correlation was established with the motive of SS (.311; p<=.01), indicating that the desire to achieve success in combination with youthful maximalism is a strong psycho-emotional formation. It is noted that such a combination has a significant mental resource for the development of young athletes. Future (F) time perspective is the most important and dependent time orientation of young athletes in general. The motivations for sports were compared among respondents with optimal (Group 2) and general time perspective profiles (Group 1). Statistical differences were found that demonstrated Group 2`s advantage on the following scales: CPM (t = 3.34; p < .01), SS (t = 3.12; p < .01), and SCM (t = 2.03; p < .05). Group 1 had a significant advantage for ?S (t = -2.42; p < .05) and SSA (t = -2.09; p < .05). The identified differences highlight the significance and role of time perspective in the development of young athletes` motivation to participate in sports. Conclusions. It has been empirically verified and substantiated that in youth, the time perspective vector moves quickly from the present to the future. It is summarized that the proposed study`s findings can increase young athletes` mental resourcefulness and help them achieve high sports results.